2023
DOI: 10.2147/opth.s425352
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Single-Masked Study of Bilateral Isofocal Optic-Design or Monofocal Intraocular Lenses

Abstract: Purpose To assess refractive and visual outcomes of bilateral implantation of an isofocal optic-design intraocular lens (IOL) or a monofocal IOL following cataract surgery. Methods A total of 127 patients were recruited into a prospective, single-masked, randomized trial. Sixty-five patients bilaterally implanted with the Isopure Isofocal IOL and 62 patients with the Micropure Monofocal IOL were followed for 4–6 months. Refraction, monocular and binocular uncorrected-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Specific data on the occurrence of photic phenomena and optic aberrations showed that in one study, 63% had no dysphotopsias, 16% experienced glare, 16% starburst, and 5% haloes ( 3 ). When ISOPURE 123 was compared with a standard monofocal MICROPURE 123 IOL, the average size and intensity of halo (from pre-op 18.31 to 27.32) and glare (from pre-op 10.34 to 18.76) phenomena were similar between the two groups ( 7 ).…”
Section: Summary Of Literature On Visual Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Specific data on the occurrence of photic phenomena and optic aberrations showed that in one study, 63% had no dysphotopsias, 16% experienced glare, 16% starburst, and 5% haloes ( 3 ). When ISOPURE 123 was compared with a standard monofocal MICROPURE 123 IOL, the average size and intensity of halo (from pre-op 18.31 to 27.32) and glare (from pre-op 10.34 to 18.76) phenomena were similar between the two groups ( 7 ).…”
Section: Summary Of Literature On Visual Performancementioning
confidence: 99%
“…In another non-comparative study, ISOPURE ® IOL, based on greater depth of focus than aspheric monofocal IOLs, offered a good option for distance and intermediate vision with fewer optical aberrations and dysphotopsias ( 6 ). In a randomised controlled trial comparing ISOPURE ® IOL with a standard monofocal aspheric IOL, both IOLs provided excellent visual acuity and contrast sensitivity for far vision with a similar frequency of photic phenomena, but, in addition, the ISOPURE IOL improved unaided intermediate vision performance ( 7 ).…”
Section: Summary Of Literature On Visual Performancementioning
confidence: 99%
“…Finally, a total of 1 meta-analysis and systematic review, 1 meta-analysis, 1 scoping review, and 19 clinical studies were considered for analysis (Table 1). 5,10–34…”
mentioning
confidence: 99%
“…Therefore, enhanced monofocal IOLs provide interchangeable results in terms of distance vision compared with conventional monofocal IOLs. 12–34…”
mentioning
confidence: 99%